LBPS 01-22 VOLATILE ORGANIC COMPOUNDS: A POTENTIAL BIOMARKER FOR PREDICTION OF HYPERTENSION POST-BARIATRIC SURGERY. (September 2016) - Azharian, Sahar; Neal, Matthew; Kyrou, Iannos; Vrbikova, Jana; Hainer, Voitech; Sramkova, Petra; Fried, Martin; Piya, Milan; Kumar, Sudesh; Covington, James; McTernan, Philip
Abstract : Objective: Human obesity can significantly contribute to hypertension risk, often referred to as the "silent killer", although targeting whom with weight gain becomes clinically hypertensive is unclear. Whilst therapeutic intervention such as bariatric surgery can mitigate both obesity and hypertension, it is not the most suitable solution for all patients. Therefore an early biomarker detection system to assess hypertension in subjects with weight gain could reduce mortality risk. Such a platform could be developed through a urine centred biomarker system identifying disease related signatures based upon volatile organic compounds (VOCs). The focus of this study was to determine whether urinary VOCs could be used as a potential monitoring tool for detection of blood pressure change in obese- hypertensive bariatric patients. Design and Method: Pre-surgery urine of 23 obese female patients undergoing bariatric surgery was analysed by Field-Asymmetric Ion Mobility Spectrometer (FAIMS). The data was processed by dividing the cohort into two classifications (high and low) based on individual median values: systolic and diastolic blood pressure, mean arterial pressure (MAP), C-reactive protein (CRP) and heart rate. Support Vector Machine (SVM) classifiers were trained with features selected using the Wilcoxon rank sum test. Performance was assessed using 10-fold cross-validation and the area under the ROC curve (AUC). Results: FAIMS urinary VOC analysis highlighted a significant association with blood pressure markers as determined by systolic (ROC curve AUC: 0.918, p < 0.001), MAP (AUC: 0.845 p < 0.001), CRP (AUC: 0.932, p < 0.001) and heart rate (AUC: 0.945, p < 0.001); whilst diastolic did not attain significance (AUC: 0., p = N.S). Additionally the VOCs have predicted change in blood pressure factors 6 months post surgery. Conclusions: This study suggests that urinary VOCs can be used for monitoring change in blood pressure in bariatric patients, additionally this technique could be utilised as a novel-screening tool for prediction of hypertension risk in subjects.